Biogenic Synthesis of Novel Functionalized Selenium Nanoparticles by Lactobacillus casei ATCC 393 and Its Protective Effects on Intestinal Barrier Dysfunction Caused by Enterotoxigenic Escherichia coli K88 - Xu, Chunlan; Guo, Yu; Qiao, Lei; Ma, Li; Cheng, Yiyi; Roman, Alexandra (Frontiers in Microbiology, 2018)
Selenium (Se) is an essential element for human and animal health. Biogenic selenium nanoparticles (SeNPs) by microorganism possess unique physical and chemical properties and biological activities compared with inorganic selenium and organic selenium. The study was conducted to investigate the mainly biological activities of SeNPs by Lactobacillus casei ATCC 393 (L.casei 393). The results showed that L.casei 393 transformed sodium selenite to red SeNPs with the size of 50 80 nm, and accumulated them intracellularly. L.casei 393-SeNPs promoted the growth and proliferation of porcine intestinal epithelial cells (IPEC-J2), human colonic epithelial cells (NCM460) and human acute monocytic leukemia cell (THP-1)–derived macrophagocyte. L.casei 393-SeNPs significantly inhibited the growth of human liver tumor cell line-HepG2, and alleviated diquat-induced IPEC-J2 oxidative damage. Moreover, In vivo and in vitro experimental results showed that administration with L.casei 393-SeNPs protected against Enterotoxigenic Escherichia coli K88 (ETEC K88)–caused intestinal barrier dysfunction. ETEC K88 infection-associateed oxidative stress (glutathione peroxidase (GPx) activity, total superoxide dismutase (T-SOD) activity, total antioxidant capacity (T-AOC), and malondialdehyde (MDA)) were ameliorated in L.casei 393-SeNPs-treated mice. These findings suggest that L.casei 393-SeNPs with no cytotoxity play a key role in maintaining intestinal epithelial integrity and intestinal microflora balance in response to oxidative stress and infection.